2021
DOI: 10.3390/ijerph18147353
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Indoor Environmental and Social Comfort of Outpatient Staff during the COVID-19 Pandemic, an Explanatory Study

Abstract: While the pressure on hospital workers keeps growing, they are generally more dissatisfied with their comfort than other occupants in hospitals or offices. To better understand the comfort of outpatient workers in hospitals, clusters for preferences and perceptions of the indoor environmental quality (IEQ) and social comfort were identified in a previous study before the outbreak of the coronavirus disease 2019 (COVID-19) pandemic. This qualitative study explains the outpatient workers’ main preferences for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The COVID-19 pandemic, which started when the design of the hubs was established, showed the importance of face-to-face contact in hospitals. For example, impoverished interaction was one of the main complaints of hospital workers during the COVID-19 pandemic and was associated with the quality of care and work satisfaction (Eijkelenboom, Ortiz, and Bluyssen, 2021). As the experience centre was delivered recently (2021) and the main building will open in September 2022, evaluation of wellbeing in relation to the EBD principles is not yet possible.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic, which started when the design of the hubs was established, showed the importance of face-to-face contact in hospitals. For example, impoverished interaction was one of the main complaints of hospital workers during the COVID-19 pandemic and was associated with the quality of care and work satisfaction (Eijkelenboom, Ortiz, and Bluyssen, 2021). As the experience centre was delivered recently (2021) and the main building will open in September 2022, evaluation of wellbeing in relation to the EBD principles is not yet possible.…”
Section: Discussionmentioning
confidence: 99%
“…Items D2: Performance management, D3: Information mechanism, and D5: Training mechanism had relatively large coefficients of observed variables, which indicated that the establishment and improvement of the symbiosis model was of great significance to the effect of the integration of medical and disease prevention in public hospitals. Through the performance management of employees in public hospitals, it was helpful to encourage clinical employees to participate in the integration of medical and disease prevention, thereby improving the effect of the integration of medical and disease prevention [42].…”
Section: Symbiotic Model Significantly Positively Affected the Effect...mentioning
confidence: 99%
“…To limit infection risk during the COVID-19 pandemic, some small physical adaptations of furniture were executed, such as stanchions in front of the reception desk or a splash guard at the reception (Eijkelenboom, Ortiz, and Bluyssen, 2021). Therefore, those working at a reception desk found it more difficult to support the privacy of the patients because they had to talk louder.…”
Section: Figure 4 Main Preferences Logic Of Ranking and Changesmentioning
confidence: 99%
“…Other changes, not related to the building characteristics of the outpatient area, were sensitization and working in other areas, e.g., testing for corona infections or working at home. Those who worked from home and others who worked at the hospital, were missing face-face contact with patients and colleagues (Eijkelenboom, Ortiz and Bluyssen, 2021). They found face-to-face contact especially important because it contributed to their work satisfaction.…”
Section: Figure 4 Main Preferences Logic Of Ranking and Changesmentioning
confidence: 99%